PENERAPAN ASAS TRANSPARANSI DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH - Purwanto Purwanto (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
The purpose of this study was to determine the application of the principle of transparency in the delivery of local government in the province of Gorontalo Pohuwato and to determine the factors that affect the application of the principle of transparency . Application of the principle of transparency in local governance which have not been running as mandated by Act No. 32 of 2004 on Regional Government does not operate effectively . The factors that lead to ineffective application of the principle of transparency in local governance in Pohuwato are a lack of personnel resources and the limited facilities and infrastructure .